Radiation emissivity and greenhouse effect due to urban occupation of land in the Una River Basin, São Paulo - Moreno, Argemiro [UNESP]; Lourenço, Roberto [UNESP] (Universidad Nacional de Colombia, 2018)
Watersheds are undergoing modifications in their natural cover that affect their surface physical properties, such as the radiation emissivity. To analyse this phenomenon, satellite images were used to interpret the land occupation by urban buildings in the basin of the river Una, São Paulo. The influence of the identified areas on the behaviour of the radiation emitted by the identified urban zones was then estimated. For this purpose, the Stefan-Boltzman law was applied by geoprocessing Landsat 8 images. The anthropic impact of the buildings was identified when the increase in the radiation emission in the basin was observed, in contrast to that of the preserved natural areas. As a result, conditions were observed that could affect the greenhouse effect that regulates the temperature of the biosphere.
Emisividad de radiación y efecto invernadero por la ocupación urbana del suelo en la Cuenca del río Una, São Paulo
Emissividade de radiação e efeito estufa pela ocupação urbana do solo da bacia hidrográfica do rio Una, São Paulo
Keywords: Climate change; Emitted radiation; Greenhouse effect; Urban buildings; Watersheds